Hydroisomerization and Hydrocracking of n-Heptane over Nanoporous Trimetallic (Pt-Ni-Co/SBA-15 Catalyst) - Talib M.Albayati; Aidan M. Doyle (Engineering and Technology Journal, 2013)
The heterogeneous hydroisomerization and hydrocracking of n-heptane was carried out within the pores of the mesoporous SBA-15 silicas, within which was encapsulated trimetallic nanoparticles of Pt-Ni-Co. The structural and textural features of the nanoporoussilicas, both with and without encapsulated nanoparticles, were characterised using small angle X-ray diffraction, scanning electron microscopy (SEM), EDAX, nitrogen adsorption-desorptionporosimetry/BET surface area analysis,Fourier-transform infrared (FTIR) spectroscopyand transmission electron microscopy (TEM).Catalytic testing was conducted using a plug-flow reactor in a catalyst testing rig under tightly controlled conditions of temperature, reactant flow rate and pressure.Species were leaving the reactor andanalysed by Gas Chromatography. The results show thatPt-Ni-Co/SBA-15 had a high activity for conversion of n-heptane (around 85%). The catalyst was found to be stable to heating and did not undergo any significant deactivation during reaction at temperatures up to 400 °C.